T. N. Godavaraman Case: A Study (Global Journal of Human-Social Science, 2015)
ontribution role of T N Godavaraman Thirumulpad in protection and conservation of environment especially with respect to forests in India has beenprodigious Popularly known as the Green Man he assured through various methods like filing of varied PILs and interceding in numerous projects that legitimate harmony could be accomplished between consumption of resources and conservation of the same exclusively conservation of forests Environmental law being a field of national importance has attracted a great deal of participation from different NGOs private organization apex court and most importantly the common man without whose contribution and support ideal environmental conditions cannot be attained The Supreme Court of India has always acted as a catalyst to back support the growth and development of the environment through ensuring the protection of all components of environment by generating new jurisprudences like that of absolute liability doctrine and adding international concepts of sustainable development precautionary principle and polluter pay principle
Keywords: consumption of resources and conservation of the same; exclusively conservation of forests